Surgical treatment of HCC in a patient with lamivudine-resistant hepatitis B cirrhosis with adefovir dipivoxil - Akima, Takashi (Baishideng Publishing Group Co., Limited, 2010)
We describe a 77-year-old woman with chronic hepatitis B who became resistant to lamivudine. She was started on adefovir (10 mg daily) while still continuing lamivudine therapy. Four mo later her liver function improved and serum Hepatitis B virus (HBV)-DNA level became undetectable. Three years after the start of additional adefovir treatment, hepatocellular carcinoma (HCC) was detected and the patient underwent a successful hepatectomy. Our findings suggest that the addition of adefovir to ongoing lamivudine therapy cannot completely suppress hepatocarcinogenesis, but is useful for improving liver function in patients with lamivudine-resistant HBV-related cirrhosis, allowing HCC surgery.